PENGARUH BAHAN BAKAR PREMIUM, PERTAMAX, PERTAMAX PLUS DAN VARIASI RASIO KOMPRESI TERHADAP KADAR EMISI GAS BUANG CO DAN HC PADA SUZUKI SHOGUN FL 125 SP TAHUN 2007 - Eko Winarto; Husin Bugis; C. Sudibyo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2013)
The purpose of this research: (1) Investigated the motorcycle exhaust emissions Suzuki Shogun FL 125 SP in 2007 used premium,pertamax,and pertamax plus. (2) Investigated the motorcycle exhaust emissions Suzuki Shogun FL 125 SP in 2007 used variation of compression ratio. (3) Investigated the motorcycle exhaust emissions Suzuki Shogun FL 125 SP in 2007 used interaction premium,pertamax, pertamax plus, and variation of compression ratio.This research was used experimental methods.The research was measurement at the Laboratory of Automotive Mechanical Engineering Education Program, JPTK, FKIP, UNS Surakarta to the address on Ahmad Yani road no. 200 Kartasura. Test of CO and HC exhaust gas emissions was used a gas analyzer type STARGAS 898. The population in this research was a motorcycle Suzuki Shogun FL 125 SP in 2007 and the sample in this research was a motorcycle Suzuki Shogun FL 125 SP in 2007 with engine number: F4A1ID113687.Based on this researchcan be concluded: (1) The measurement premium fuel producedthe lowest emission in CO 3.884% by 9.1:1 compression ratio and the the lowestexhaust gas emission levels in 168 ppmby 9.1:1 compression ratio. (2) The measurement pertamax fuel produced the lowest exhaust gas emission levels in CO 3.237% by 9.5:1 compression ratio and the the lowest exhaust gas emission levels in 210 ppm by 9.5:1 compression ratio(3) The measurement pertamax plus fuel produces the lowest exhaust gas emission levels in CO 2.615% by 10.2:1 compression ratio and the the lowest exhaust gas emission levels in 237 ppm by 9.5:1 compression ratio